ARCH-COMP22 Category Report: Stochastic Models - Abate, Alessandro; Blom, Henk; Delicaris, Joanna; Haesaert, Sofie; Hartmanns, Arnd; van Huijgevoort, Birgit; Lavaei, Abolfazl; Ma, Hao; Niehage, Mathis; Remke, Anne; Schön, Oliver; Schupp, Stefan; et al. (EPiC Series in Computing)
This report presents the results of a friendly competition for formal verification and policy synthesis of stochastic models. It also introduces new benchmarks and their properties within this category and recommends next steps for this category towards next year’s edition of the competition. In comparison with tools on non-probabilistic models, the tools for stochastic models are at the early stages of development that do not allow full competition on a standard set of benchmarks. We report on an initiative to collect a set of minimal benchmarks that all such tools can run, thus facilitating the comparison between efficiency of the implemented techniques. The friendly competition took place as part of the workshop Applied Verification for Continuous and Hybrid Systems (ARCH) in Summer 2022.

Increasing Intelligent Systems’ Reliability by using Reconfiguration - Meyer, Tobias; Kessler, Jan Henning; Sextro, Walter; Trächtler, Ansgar (The Annual Reliability and Maintainability Symposium (RAMS))
Self-optimizing mechatronic systems allow the adaptation of the system’s behavior to the current situation. This can be used to actively adapt the behavior to the current degradation state of the system or of some of its components. To this end, the Multi-Level Dependability Concept has been developed. In this contribution, we show how the Multi-Level Dependability Concept has been applied to the active suspension module of an innovative rail-bound vehicle. For this module, the usage of control reconfiguration, which is a novel approach to exploit complex redundancy systems, is required. We show that by combining self-optimization with the possibilities given by control reconfiguration, the dependability of a complex mechatronic system can be greatly improved.

Zuverlässigkeitsorientierte Mehrzieloptimierung zur Aktorrekonfiguration eines X-by-wire-Fahrzeugs - Sondermann-Wölke, Christoph; Sextro, Walter; Reinold, Peter; Trächtler, Ansgar (Technische Zuverlässigkeit TTZ)

Eine Reduktionsmethode zur Ableitung elektromechanischer Ersatzmodelle für piezoelektrische Wandler unter Verwendung der Finite-Elemente- Methode (FEM) - Krol, Rafal